Converting tropical rainforest to native rubber plantations alters soil bacterial and fungal communities - Ling-ling Shi; De-Li Zhai; Hua-fang Chen (Circular Agricultural Systems, 2022)
Driven by soil biochemistry and plant community composition, soil microbial communities reflect land management and environmental conditions. To evaluate the effects of land-use change on soil microbial diversity, we used denaturing gradient gel electrophoresis (DGGE) combined with sequencing to compare bacterial and fungal community profiles between rubber plantation (RP) and nearby seasonal rainforests (SR). Rainforest soil generally had higher soil total C and microbial biomass C concentration, smaller soil aggregate proportions, and a soil pH below rubber plantation soil. The bacterial and fungal richness and diversity were similar after converting primary forests to rubber plantations. However, the composition of bacterial and fungal communities has significantly changed in rubber plantations. Basidiomycota, the predominant group of fungi, was significantly different between primary forests and rubber plantations. However, Basidiomycota showed higher heterogenetic distribution in the rainforest under rubber plantations. In conclusion, land-use changes mainly affect soil microbial community composition and heterogeneity distribution patterns, especially for saprotrophic fungi, which consist of changes in litter inputs and soil C conditions.